2017
DOI: 10.1021/acs.energyfuels.7b02704
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation and Simulation Modeling of Polymer Flooding in High-Temperature, High-Salinity Carbonate Reservoirs

Abstract: Polymer flooding is one of the most commonly employed improved oil-recovery techniques. However, its successful application is related to favorable reservoir conditions and geology. In addition, its application in high-temperature, high-salinity (HT-HS) carbonate reservoirs is still a challenging task. A series of laboratory core-flood experiments have been performed at reservoir conditions (temperature of 120 °C and salinity of 167 g/L) on carbonate outcrop core samples to evaluate the flow behavior of polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Hence, the contribution of polymer/nanoparticle toward recovery factor should not be ignored. The secondary and tertiary flooding data results were employed as input data for (CMOST) assisted history‐matching functions, discussed in subsequent sections 18,19,27,40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the contribution of polymer/nanoparticle toward recovery factor should not be ignored. The secondary and tertiary flooding data results were employed as input data for (CMOST) assisted history‐matching functions, discussed in subsequent sections 18,19,27,40 …”
Section: Resultsmentioning
confidence: 99%
“…Janssen et al found that CMG simulation model is useful to determine displacement phenomena governing flooding behavior, depending on injection fluid type 39 . The effectiveness of numerical simulation studies on chemical flooding showed far‐reaching consequences during oilfield applications, as evident from the findings of earlier papers 37,40 . This kind of grid‐based model helps in understanding fluid flow behavior prior to injection; as well as achieve a sufficiently robust model 36,38,39 .…”
Section: Experimental and Simulationmentioning
confidence: 99%
“…Identifying a polymer that can withstand hightemperature and high-salinity conditions is a major step for a successful polymer-flooding application (Hashmet, AlSumaiti, Qaiser & AlAmeri, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oil field water often contains a great quantity of salts and high salinity can greatly affect the viscosity of polymer solution, especially Ca 2+ and Mg 2+ . In such a complex strata environment, including high temperature, high shear rate, and high salinity, the hydrodynamic volume of polymer decreases, resulting in a decrease in viscosity and inability to carry proppant. Thus, stabilization of polymers in formation of environment with high temperature, high shear rate, and high salinity is an important ongoing issue for petroleum industry.…”
Section: Introductionmentioning
confidence: 99%